Linguistic Signs of The Names of Leaves Used by Sikerei in Maileppet South Siberut Mentawai - Astuti, Amelia Yuli; Roberto, Mikael (Jurnal Ilmiah Langue and Parole, 2024)
This research is entitled " Linguistic Signs of the Names of Leaves Used by Sikerei in Mailepppet, South Siberut, Mentawai. This research is limited to several main ideas related to the observation of the following two questions: What are the signifier and signified of the leaves used by Sikerei in rituals in Maileppet, South Siberut, Mentawai. To explain the signifier and signified of the meaning of the leaves used by Sikerei in rituals in Maileppet, South Siberut, Mentawai. The theory used comes from Saussure's theory and Barthes' theory which is used to dissect and get answers to the objectives of this research. For the data analysis method, the author uses qualitative research by emphasizing meaning and significance in certain conditions. This research uses data collection techniques in the form of field observations, interviews, notes, voice recordings, photos. The conclusion of this research is the meaning of the leaves used by Sikerei in rituals in Maileppet, South Siberut, Mentawai. The arat sabulungan belief means belief in objects that have the spirit of the cultural heritage of the Mentawai people's ancestors. This belief is the same as the unwritten norms or rules for the Mentawai people which guide the daily life of the Mentawai people, especially in Maileppet, South Siberut.